Upper Troncoso Member Evapofacies of the Huitrín Formation (Lower Cretaceous, Neuquén Basin, Argentine): palaeoenvironments, evolution and controls (Latin American Journal of Sedimentology and Basin Analysis, 2021)
This contribution presents a characterization of Barremian evaporite facies of the Neuquén Basin (western Argentina) in order to discuss accumulation processes and depositional conditions. The evapo- rite accumulation is related to a proto-Pacific trans- gression that followed an Early Barremian widespread desiccation event. These evaporites are known as the Upper Troncoso Member of the Huitrín Formation. They constitute a research topic of great importance, both from the theoretical point of view (stratigraphy, origin, palaeoclimate), as well as from the knowledge of non-renewable natural resources (celestine - barite, anhydrite - gypsum, rock salt, potassium salts and hydrocarbons). The Neuquén Basin is considered an ensialic backarc basin associated with the easterly oriented subduction along the proto-Pacific margin of Gond- wana (Figs. 1, 4). A generalised extensional stress regime due to steep subduction angle occurred in the magmatic arc and in the backarc settings, although regional thermal subsidence was punctuated by several episodes of structural inversion. Thus, the Upper Troncoso evaporites represent an unique example of accumulation in a marginal marine basin linked to the active continental margin of western Gondwana (Figs. 3, 4).The Lower Cretaceous deposits of the Huitrín Formation crop out almost continuously for more than 500 km along a north-south oriented belt (Fig. 5), from the latitude of the Aconcagua Mountain (Mendoza Province) up to the vicinity of the city of Zapala (Neuquén Province). Owing to the highest solubility and hygroscopic characteristics of the sediments, combined with the strong tectonic dis- turbation of the Huitrín Formation, the methodology for the study of the evaporites was largely based on subsurface information (geophysical well-log responses, cutting and cores) taken from oil and potassium salt exploration drill holes. In particular, electric logs allowed to identify electrofacies, and -based on the interpretation of cross-plots- to infer the mineralogy of the evaporites. Together with lithological descriptions of cutting and cores, repre- sentative samples of the rocks were studied in thin sections and by X-ray diffractometry. In the latter both whole-rock composition and
Keywords: Barremian evaporites, Depositional sys- tem, Upper Troncoso Member (Huitrín Formation), Neuquén Basin, Argentine.